Teaching Grammatical Rules using The Syarh Alfiyyah Ibn Malik by Ibn 'Aqil - Ahyarudin, Ahyarudin; Faisol, Faisol; Mufidah, Nuril (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2024)
This study aims to find out the teaching steps of Grammatical Rules using the book of Sharh Ibn Aqil Ala Alfiyah Ibn Malik. This research is qualitative with descriptive method, this research is located in ma'had Al-Jihad West Bandung. The method of collecting and analyzing data researchers use the method presented by Mills and Huberman: data collection, data classification, presentation, and conclusion. The research sample is the teachers of qawaid nahwiyah and 1st grade high school students at ma'had Al-Jihad. the researcher concluded the results that the steps in teaching al qawaid an-nahwiyah are carried out through the following stages, 1).The preparation of qawaid nahwiyah learning materials before teaching. 2). identifying the topic to be studied. 3) setting the time of the learning process.